2001
DOI: 10.1046/j.1365-2044.2001.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new percutaneous dilatational tracheostomy set

Abstract: SummaryPercutaneous tracheostomy is a well established technique used primarily to assist weaning from mechanical ventilation on many intensive care units. We report our experiences of a total of 36 procedures performed with the new Blue Rhinoe Percutaneous Tracheostomy Introducer Set developed by Ciaglia. The technique was successful in all cases and was simpler and quicker to perform than with the earlier Ciaglia percutaneous tracheostomy set. Difficulties were encountered when using Shileye tracheostomy tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 8 publications
(6 reference statements)
0
20
0
Order By: Relevance
“…Based on our findings, arming the PercuTwist guidewire with an 8-F guiding catheter in the same manner as the Blue Rhino guidewire may significantly enhance the safety of the PercuTwist technique. Nonetheless, even with a guiding catheter, kinking of the guidewire/catheter unit with subsequent posterior tracheal wall injury has been reported during Blue Rhino tracheostomy [13], although serious complications with the latter technique were not observed in the recent study. With the exception of these three major or intermediate complication in the PercuTwist group described above, a few minor complications and difficulties were observed in the two groups with similar incidence.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Based on our findings, arming the PercuTwist guidewire with an 8-F guiding catheter in the same manner as the Blue Rhino guidewire may significantly enhance the safety of the PercuTwist technique. Nonetheless, even with a guiding catheter, kinking of the guidewire/catheter unit with subsequent posterior tracheal wall injury has been reported during Blue Rhino tracheostomy [13], although serious complications with the latter technique were not observed in the recent study. With the exception of these three major or intermediate complication in the PercuTwist group described above, a few minor complications and difficulties were observed in the two groups with similar incidence.…”
Section: Discussionmentioning
confidence: 83%
“…Severe hemorrhage, damage to the posterior tracheal wall, and loss of airway are the most threatening complications of multistep procedures [3,4,5,6]. The newer methods of percutaneous tracheostomy such as TLT, Blue Rhino, and PercuTwist are single-step techniques and are intended to cause fewer and less severe complications [6,7,8,9,10,11,13]. A recent analysis of prospective studies on percutaneous tracheostomy reported a rate of serious complications below 3% for the single-step techniques of TLT and Blue Rhino [9].…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties with the single dilator Blue Rhino™ technique have been reported in the past, particularly when used in conjunction with the Shiley tracheostomy tubes [11]. Methods to overcome this problem by using alternative tracheostomy tubes have also been described [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…This technique uses a simpler kit with fewer parts than the original kit and requires fewer dilation attempts, making it faster. 14 This technique has been imitated by other manufacturers and is widely used in the UK.…”
Section: Tracheostomymentioning
confidence: 99%